Review of Research into Explicit and Implicit Learning of English - Judytková, Veronika (Univerzita Pardubice, 2024)
This bachelor thesis focuses on explicit and implicit learning of languages in the context of second language acquisition. The theoretical part deals with defining second language acquisition, presenting second language acquisition perspectives and describing explicit and implicit learning and knowledge. The practical part aims to structure a traditional review to answer established research questions about implicit learning of English.
Explicitní a implicitní učení anglického jazyka: přehledová studie
Keywords: osvojování druhého jazyka; nevědomé učení; vědomé učení; second language acquisition; implicit learning; explicit learning